National Inmate Survey (NIS) - Prisons: Alternative Survey Respondents Only, (United States), 2007-2009 ([Verlag nicht ermittelbar], 2019)
The National Inmate Survey (NIS) is part of the Bureau of Justice Statistics' (BJS) National Prison Rape Statistics Program, which gathers mandated data on the incidence and prevalence of sexual assault in correctional facilities under the Prison Rape Elimination Act of 2003 (PREA; P.L. 108- 79). Inmates are randomly assigned to receive either a survey of sexual victimization or a survey of mental and physical health, past drug and alcohol use, and treatment for substance abuse. The data in this study focuses solely upon substance use and treatment from the "alternative" version of the survey. These 3,908 respondents contained in this file who completed the "alternative" survey are the same 3,908 alternative respondents from the study National Inmate Survey (NIS) - Prisons: Full Survey Respondents, [United States], 2007-2009 (ICPSR 37017).